2022
DOI: 10.21608/ejoh.2021.88804.1180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tryptophan, Proline and Tyrosine on Vegetative Growth, Yield and Fruit Quality of Red Roumy grapevines

Abstract: T HIS study was achieved out during two successive seasons (2018 & 2019) on 12 yearold Red Roumy grapevines. The chosen vines were grown in a clay soil under surface irrigation system in a private vineyard at El-deer hamlet, Aga, Dakahlia region, Egypt. Three amino acids namely tryptophan, proline and tyrosine were used as foliar application at rate 100 and 200 ppm on the vines for three times, at vegetative growth start, at full bloom stage and at verison stage. Results appeared that using tryptophan, prolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…Caronia et al (2010) demonstrated that application of L-proline on Tarocco Scire trees caused an increment in TSS percentage. The total soluble solids were statistically affected by all L-proline treatments by boosting photosynthesis and chlorophyll, in agreement with the results by El Sayed et al (2014), Mahmoudi et al (2014), andEl Kenawy (2022).…”
Section: Total Soluble Solids %supporting
confidence: 91%
See 3 more Smart Citations
“…Caronia et al (2010) demonstrated that application of L-proline on Tarocco Scire trees caused an increment in TSS percentage. The total soluble solids were statistically affected by all L-proline treatments by boosting photosynthesis and chlorophyll, in agreement with the results by El Sayed et al (2014), Mahmoudi et al (2014), andEl Kenawy (2022).…”
Section: Total Soluble Solids %supporting
confidence: 91%
“…During the 2020 season, L-proline at 200 µg/ml procured the highest total sugar percentage (8.29), compared to (4.40) for the control treatment. These results are generally in line with those attained by Takeuchi et al (2008), El Sayed et al (2014, Mahmoudi et al (2014), andEl Kenawy (2022). They reported that the total sugars of fruit juice were increased by spraying L-proline, which hydrolyzed polysaccharides such as starch into fruit-reducing sugars such as fructose and glucose.…”
Section: Total Sugar %supporting
confidence: 88%
See 2 more Smart Citations
“…7 It was reported that proline at 200 ppm caused an increase of total anthocyanin of Red Roumy grapes while reduced titratable acidity. 8 It was reported that proline plays a main role in preserving the osmotic balance, stabilizing the structure of enzyme and membranes in key proteins. In addition to, Protecting the photosynthetic products and scavenging free radicals.…”
Section: Introductionmentioning
confidence: 99%